Transformasi Kehidupan: Peran Konselor Adiksi dan Pekerja Sosial dalam Proses Rehabilitasi di Panti Rehabilitasi Narkoba - Dinda Renita Sibagariang; Eflin Novita Sinaga; Silmi Sri Rosmayanti (Pusat Riset dan Inovasi Nasional, 2024)
This visit activity is the result of theoretical learning that has been explained. In understanding the roles of addiction counselors and social workers, the author used a research method involving in-depth interviews with addiction counselors and social workers. The counselor is a former user who has proven that they have escaped the brink of death. The difference in roles between addiction counselors and social workers can be seen from the tools they use; although different, they remain aligned. The goal is the same: to design rehabilitation programs aimed at helping addicts recover from their physical and psychological dependence on narcotics, alcohol, or other addictive substances.